Perbandingan Penggunaan Selimut Hangat Dan Infus Hangat Terhadap shivering Pasca Operasi Dengan General Anestesi di Instalasi Bedah Sentral RSUD Wates - Dhiyah Nabalah; Istiqomah Rosidah; Ratih Kusuma Dewi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The administration of general anesthesia during surgery may lead to side effects, including hypothermia, which can induce shivering and impact the patient's postoperative condition. Non-pharmacological interventions, including the use of warm blankets and warm infusions, are carried out to treat shivering. This study aims to investigate the effects of warm blankets and warm infusions on postoperative shivering in patients undergoing general anesthesia at the Central Surgical Installation of Wates Hospital. This study aims to investigate the effects of warm blankets and warm infusions on postoperative shivering in patients undergoing general anesthesia at the Central Surgical Installation of RSUD (Regional General Hospital) Wates. This research employed a quantitative methodology utilizing a quasi-experimental design characterized by a two-group pretest-posttest design. A total of 162 respondents reported experiencing shivering following general anesthesia. The study employed purposive sampling, resulting in a sample size of 36 respondents. The data collection employed an observation sheet, while data processing utilized the Wilcoxon signed-rank test and the Mann-Whitney test. The Wilcoxon signed rank test obtained results of (p = 0.000) for the warm blanket group and (p = 0.001) for the warm infusion group, indicating a significant effect of warm blankets and warm infusions on shivering. The hypothesis test results for the differences in the use of warm blankets and warm infusions, analyzed using the Mann Whitney test, indicated a significant difference (p = 0.001). A comparison of warm blankets and warm infusions for post-operative shivering following general anesthesia at the Central Surgery Installation of RSUD Wates indicates that warm blankets are more effective in reducing shivering.